2013
DOI: 10.1097/mej.0b013e328353d926
|View full text |Cite
|
Sign up to set email alerts
|

A clinical decision model identifies patients at risk for delayed diagnosed injuries after high-energy trauma

Abstract: Our newly developed clinical decision model can identify patients who are at a risk for delayed diagnosed injuries and who should undergo an intensified search for potential unidentified injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The risk of a missed injury increases when the patient has multiple injuries and/or the patient is unstable (7, 13). Studies have shown that head injuries (4, 6, 13, 14), mechanical ventilation (5, 8), low scores on the Glasgow Coma Scale (GCS) (2, 4, 7, 15), and high Injury Severity Scores (ISS) (2, 4, 7, 15, 16) can lead to delayed diagnosis. Inadequate clinical examinations (9, 11), departures from clinical routines (11), and misinterpreted or inadequate radiographs (2, 4, 5, 8, 11, 17) also contribute to delayed diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of a missed injury increases when the patient has multiple injuries and/or the patient is unstable (7, 13). Studies have shown that head injuries (4, 6, 13, 14), mechanical ventilation (5, 8), low scores on the Glasgow Coma Scale (GCS) (2, 4, 7, 15), and high Injury Severity Scores (ISS) (2, 4, 7, 15, 16) can lead to delayed diagnosis. Inadequate clinical examinations (9, 11), departures from clinical routines (11), and misinterpreted or inadequate radiographs (2, 4, 5, 8, 11, 17) also contribute to delayed diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of injury was classified as either highenergy trauma or low-energy trauma. 31 All other data were identified from clinical reports. The neurosurgical procedures were identified from an online register from the neurosurgical hospitals.…”
mentioning
confidence: 99%
“…6. Patients were classified as neurologically deteriorating if the GCS score decreased by at least 2 points or if onset of pupillary abnormalities (as defined by Morris et al 21 ) was registered. The mechanism of injury was classified as either high velocity trauma or low-velocity trauma.…”
Section: Clinical Data Collectionmentioning
confidence: 99%
“…17,20 The term " radiological evolution " has a scientific literature that lacks uniformity in defining it and due to different clinical studies which has reported haemorrhagic contusion progression ( 16.4 % to 51 % ), clinical definition stands controversial. 1,2,4,6,14,15,21,24 .…”
Section: Introduction:-mentioning
confidence: 99%